6x-2=x+135x=15x=3
(x - 3)(x + 5)
3h+13 = 7 3h = 7-13 3h = -6 h = -2
273 13+8 = 21 and 13*21 = 273
To solve the equation 1 + 2x + 13 = 9, you first need to simplify by combining like terms. Subtract 1 and 13 from both sides of the equation to isolate the variable term. This gives you 2x = -5. Finally, divide by 2 on both sides to solve for x, which gives you x = -5/2 or -2.5.
6x-2=x+135x=15x=3
-2 plus 5 equals +3
(x - 3)(x + 5)
3h+13 = 7 3h = 7-13 3h = -6 h = -2
9a + 4a = 26 13a = 26 a = 26/13 a = 2
x/2 = 13 - 6 so x/2 = 7 so x = 14
273 13+8 = 21 and 13*21 = 273
(2,3)
To solve the equation 1 + 2x + 13 = 9, you first need to simplify by combining like terms. Subtract 1 and 13 from both sides of the equation to isolate the variable term. This gives you 2x = -5. Finally, divide by 2 on both sides to solve for x, which gives you x = -5/2 or -2.5.
If -3q + 4 = 13 then 3q = -9 : q = -3 If 6q = 13 then q = 13/6 = 2 1/6 The question contains an anomaly and is invalid.
3
3